(3JgPjH GdCNdGbs - (3CHh RcQjG jMji Hf YOj Hf RcQjG GdajdSha GdfUQGfj GdjYbhHjs
(3ChdgG (B:s
(3bGd EYde Cf GdEfSGf ef Hjf SGFQ GdMjhGf Ph acQ hJejjR hgh CHOkG jMH ef GdGehQ CaVdgG hef GdeQGJH CTQagG hef GdebJfjGJ CfaSgG s
(3BNQgG (B:s
(3hjLJgO cd GdELJgGO ai Lejd faSg hjSJaQY ZGjI GdhSY ai WdH JeGeg aeG CbHM GdfbVi HGdbGOQ Ydi GdJeGe hGdYLR hGdMeO ddg hMOg ceG jdjb Hg hde CQGO ai YjhH GdfGS YjHkG cfbU GdbGOQjf Ydi GdJeGe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK , CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs